Digital Transformation of Islamic Religious Education: Enhancing Student Engagement through Technology-Based Learning in the United Arab Emirates - Samar A. El-Farra (https://ejournal.insuriponorogo.ac.id/, 2025)
The rapid advancement of digital technology has significantly transformed educational systems worldwide, including the field of Islamic Religious Education (IRE). In the United Arab Emirates (UAE), the integration of technology-based learning has become an important strategy for improving educational quality, promoting innovation, and increasing student engagement in classroom activities. This study examines the role of digital transformation in enhancing student engagement through technology-based learning in Islamic Religious Education in the UAE. Using a qualitative literature review approach, this study analyzes scholarly articles, educational reports, and policy documents related to digital learning, student engagement, and Islamic education. The findings indicate that technology-based learning positively contributes to students’ cognitive, emotional, and behavioral engagement by creating interactive, flexible, and student-centered learning environments. Digital platforms, multimedia resources, online discussions, educational applications, and virtual collaboration tools encourage active participation and improve students’ understanding of Islamic values and teachings. Furthermore, digital transformation supports the development of critical thinking, digital literacy, and collaborative learning skills necessary for twenty-first-century education. However, several challenges remain, including unequal technological access, teachers’ digital competency limitations, and concerns regarding maintaining spiritual and moral dimensions in online learning environments. The study concludes that successful digital transformation in Islamic Religious Education requires balanced integration between technological innovation and Islamic educational values. Institutional support, teacher professional development, and inclusive digital infrastructure are essential for maximizing the effectiveness of technology-based learning in the UAE educational context.